ANALISIS PENGARUH KEMAMPUAN DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI PUSKESMAS II KEMBARAN KABUPATEN BANYUMAS - Widyo Subagyo; Mukhadiono Mukhadiono (Prodi Keperawatan Purwokerto, 2013)
This research entitled “The Influence of Work Ability and Work Facility toward Officer Performance of Puskesmas II Kembaran Banyumas Regency”. The aim of the research is find out the influence of work ability and equipments toward officer performance, both of partially and simultantly. This research was conducted at Puskesmas II Kembaran Banyumas with the target is the officers of its office. Research method used survey method, sampling method used total sampling, data collecting method used questionnare, observation, and documentation. Data analyzed done by quantitatively used product moment correlation, partial correlation, simple linear regression, multiple regression and multiple correlation. The result of this research showed that work ability has significant influence toward officer performance. It was showed that work ability have important role to support officer performance. Work facility has significant influence toward officer performance. It was showed that equipments can be support reach of satisfying performance. Work ability and work facility simultantly have significant influence toward officer performance. It was showed that the convergence of work ability and equipments will give significant influence toward officer performance. Based from the results, so all of proposed hypothesis was accepted.